Analisis Strategi Pemasaran Bandrek Esa Untuk Meningkatkan Penjualan Di Era Digital - Yuliarman, Putri Yuliarman; Radhika Narwastu; Zahratun Nisa; Muhammad Ikrom Nasution; Haliza Rahmania Putri; Friska Febiola Aritonang (Jurnal Manajemen dan Pemasaran, 2025)
The abstract of this research aims to analyze effective marketing strategies to boost sales of Bandrek Esa, a traditional Indonesian drink, in the digital era. With the rise of bold platforms and changing consumer behavior towards digital transactions, small and medium businesses need to adapt their marketing approach to remain competitive. By leveraging digital marketing tools such as social media, e-commerce platforms and targeted advertising, this research seeks to identify the most impactful methods for increasing brand awareness and customer engagement. A mixed approach was used, combining qualitative interviews with business owners and quantitative data analysis of bold sales patterns. These findings provide practical insights for Bandrek Esa producers on how to harness the power of digital marketing to drive sales growth and maintain customer loyalty in a rapidly growing market.